2007
DOI: 10.1002/cm.20251
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of actin mechanics by caldesmon and tropomyosin

Abstract: The ability of cells to sense and respond to physiological forces relies on the actin cytoskeleton, a dynamic structure that can directly convert forces into biochemical signals. Because of the association of muscle actin-binding proteins (ABPs) may affect F-actin and hence cytoskeleton mechanics, we investigated the effects of several ABPs on the mechanical properties of the actin filaments. The structural interactions between ABPs and helical actin filaments can vary between interstrand interactions that bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
38
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 54 publications
9
38
1
Order By: Relevance
“…Caldesmon is a likely candidate that is known to stabilize actin stress fibers and regulate actomyosin-mediated contractility (23,26). It has been shown recently to be a potent suppressor of podosome formation (14,24) and, like p53, is downregulated in many cancer cells (43,47,49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caldesmon is a likely candidate that is known to stabilize actin stress fibers and regulate actomyosin-mediated contractility (23,26). It has been shown recently to be a potent suppressor of podosome formation (14,24) and, like p53, is downregulated in many cancer cells (43,47,49).…”
Section: Discussionmentioning
confidence: 99%
“…Caldesmon is a calmodulin-and actin-binding protein (48) whose roles in modulating the dynamics of the actin cytoskeleton and contractility during cell movement are well documented (23,26). We and others (14,24,39) have recently shown that caldesmon negatively regulates the formation of podosomes and rosettes by vascular smooth muscle cells (SMC) transformed with Src.…”
mentioning
confidence: 99%
“…Tropomyosin is another component of the actin cytoskeleton in the hyphal tip. This protein stabilizes F-actin and controls F-actin mechanics, regulating the interaction between F-actin and myosins (215)(216)(217).…”
Section: The Actin Cytoskeletonmentioning
confidence: 99%
“…A survey of DNA sequences recognized by p53 reveals that the promoter site of caldesmon, an actin-binding protein found in podosomes, contains the consensus recognition site by p53 (unpublished data). Caldesmon is a calmodulin-and actinbinding protein 7 that is known to inhibit acto-myosin ATPase activity and cell contractility, stabilize actin stress fibers and destabilize Arp2/3-mediated actin nucleation. 8 Caldesmon was first shown to be a component of podosomes in 1993, 9 and more recently, it has been shown to play an antagonistic role in podosome formation 10,11 and its expression is downregulated in cancer cells.…”
Section: Cell Cycle Featuresmentioning
confidence: 99%